2008
DOI: 10.1080/03031853.2008.9523806
|View full text |Cite
|
Sign up to set email alerts
|

Logistic modelling of smallholder livestock farmers' adoption of tree-based fodder technology in Zimbabwe

Abstract: Based on field data collected from 131 small scale dairy farmers that were randomly selected from four agro-ecological zones, this study assessed the potential of adoption of fodder bank technology as a means for improving livestock production and income generation for smallholder farmers in Zimbabwe. Using a logit modelling approach, it also identified the drivers of adoption of the technology by analysing the influence of household characteristics and ecological factors on farmers' decision to adopt the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 14 publications
3
37
1
Order By: Relevance
“…This means that older farmers are less likely to adopt CA than the younger ones. This is inconsistent with studies by Jera and Ajayi (2008) and Ng'ombe et al (2014) who found a positive correlation between age and CA adoption. Ownership of labour saving equipment such as rippers coupled with the prestige associated with owning such implements increased the likelihood of adopting CA.…”
Section: Literature Reviewcontrasting
confidence: 56%
See 3 more Smart Citations
“…This means that older farmers are less likely to adopt CA than the younger ones. This is inconsistent with studies by Jera and Ajayi (2008) and Ng'ombe et al (2014) who found a positive correlation between age and CA adoption. Ownership of labour saving equipment such as rippers coupled with the prestige associated with owning such implements increased the likelihood of adopting CA.…”
Section: Literature Reviewcontrasting
confidence: 56%
“…Studies have also shown that over representation of men in programmes involving new innovations is linked with strong traditional and cultural practices that distinguish gender roles in agriculture mostly biased towards men (Nkala, 2012). Female headed households therefore may respond less favorably to new technology than male headed households because the traditional power structure and controls over household productive resources are less favorable to women (Jera & Ajayi, 2008). Female headed households are more likely to face a bigger constraint in terms of land and other resources.…”
Section: Demographic Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the factors affecting farmers' adoption of dairy technology is critical to success of development and implementation of policies and programmes in dairy industry development. Previous adoptionoriented research has examined the use and diffusion of dairy-related technologies (Metz et al 1995, Nicholson et al 1999Mohi and Bhatti 2006;Mekonnen et al 2009) and the factors affecting adoption on smallholder farms (Irungu et al 1998;Jera and Ajayi. 2008).…”
Section: Introductionmentioning
confidence: 99%